Assessing the Competency Readiness of Mechanical Executives in the Sewerage Industry - Harolanuar, Muhammad Nur Hanafi; Nur Yunus, Faizal Amin; Kamis, Arasinah; Hussin, Azman (Journal of Technical Education and Training, 2025)
In the era of globalization, the sewerage industry plays an important role in ensuring environmental sustainability. However, a major challenge is the skills mismatch between university graduates and industry needs. Therefore, this study is significant because graduate skills play a crucial role in meeting industry needs, especially in the sewerage sector. By understanding the level of competence and skills that should be focused on for mechanical engineering graduates and mechanical engineering technology students, the development of job structures related to the sewerage industry can be improved from the outset. This study employs a quantitative approach using the survey method. A total of 189 samples representing the Universiti Tun Hussein Onn Malaysia and Universiti Teknikal Melaka were selected using a simple random sampling technique, and their findings were analysed descriptively. All research data obtained was analysed using SPSS software to obtain frequency values, mean scores, percentages, standard deviations, and analyses of differences between the two program groups. The result of descriptive statistics analysis (mean) indicates a high level of the existing knowledge competency, basic skills competency behavioural attitude, and habitual behaviour. Results of Mann-Whitney U test indicate a significant difference in the technical skill levels between mechanical engineering and mechanical engineering technology students with higher technical skills among the mechanical engineering programs. This study is expected to provide useful input for policymakers, educational institutions, and the sewerage industry, and help address the issue of unemployment and skill mismatch in Malaysia as a whole.